Acute diabetic neuropathy following improved glycaemic control: a case series and review. (26th February 2020) - Siddique, N; Durcan, R; Smyth, S; Tun, T Kyaw; Sreenan, S; McDermott, J H
Abstract : Summary: We present three cases of acute diabetic neuropathy and highlight a potentially underappreciated link between tightening of glycaemic control and acute neuropathies in patients with diabetes. Case 1: A 56-year-old male with poorly controlled type 2 diabetes (T2DM) was commenced on basal-bolus insulin. He presented 6 weeks later with a diffuse painful sensory neuropathy and postural hypotension. He was diagnosed with treatment-induced neuropathy (TIN, insulin neuritis) and obtained symptomatic relief from pregabalin. Case 2: A 67-year-old male with T2DM and chronic hyperglycaemia presented with left lower limb pain, weakness and weight loss shortly after achieving target glycaemia with oral anti-hyperglycaemics. Neurological examination and neuro-electrophysiological studies suggested diabetic lumbosacral radiculo-plexus neuropathy (DLPRN, diabetic amyotrophy). Pain and weakness resolved over time. Case 3: A 58-year-old male was admitted with blurred vision diplopia and complete ptosis of the right eye, with intact pupillary reflexes, shortly after intensification of glucose-lowering treatment with an SGLT2 inhibitor as adjunct to metformin. He was diagnosed with a pupil-sparing third nerve palsy secondary to diabetic mononeuritis which improved over time. While all three acute neuropathies have been previously well described, all are rare and require a high index of clinical suspicion as they are essentially a diagnosis of exclusion. Interestingly, all three of our cases are linked by the development of acute neuropathy following a significant improvement in glycaemic control. This phenomenon is well described in TIN, but not previously highlighted in other acute neuropathies. Learning points: A link between acute tightening of glycaemic control and acute neuropathies has not been well described in literature. Clinicians caring for patients with diabetes who develop otherwise unexplained neurologic symptoms following a tightening of glycaemic control should consider the possibility of an acute diabetic neuropathy. Early recognition of these neuropathies can obviate the need for detailed and expensive investigations and allow for early institution of appropriate pain-relieving medications.